Co-occurrence of chronic traumatic encephalopathy and prion disease - Satish Kumar Nemani; Silvio Notari; Ignazio Cali; Victor E Alvarez; Diane Kofskey; Mark Cohen; Robert A. Stern; Brian Appleby; Joseph Abrams; Lawrence Schonberger; Ann McKee; Pierluigi Gambetti (Acta Neuropathologica Communications, 2018)
Abstract Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with repetitive traumatic brain injury (TBI). CTE is generally found in athletes participating in contact sports and military personnel exposed to explosive blasts but can also affect civilians. Clinically and pathologically, CTE overlaps with post-traumatic stress disorder (PTSD), a term mostly used in a clinical context. The histopathology of CTE is defined by the deposition of hyperphosphorylated tau protein in neurons and astrocytes preferentially with perivascular distribution and at the depths of the cortical sulci. In addition to hyperphosphorylated tau, other pathologic proteins are deposited in CTE, including amyloid β (Aβ), transactive response (TAR) DNA-binding protein 43 kDa (TDP-43) and α-synuclein. However, the coexistence of prion disease in CTE has not been observed. We report three cases of histopathologically validated CTE with co-existing sporadic prion disease. Two were identified in a cohort of 55 pathologically verified cases of CTE submitted to the CTE Center of Boston University. One was identified among brain tissues submitted to the National Prion Disease Pathology Surveillance Center of Case Western Reserve University. The histopathological phenotype and properties of the abnormal, disease-related prion protein (PrPD) of the three CTE cases were examined using lesion profile, immunohistochemistry, electrophoresis and conformational tests. Subjects with sporadic Creutzfeldt-Jakob disease (sCJD) matched for age, PrP genotype and PrPD type were used as controls. The histopathology phenotype and PrPD properties of the three CTE subjects showed no significant differences from their respective sCJD controls suggesting that recurring neurotrauma or coexisting CTE pathology did not detectably impact the prion disease phenotype and PrPD conformational characteristics. Based on the reported incidence of sporadic prion disease, the detection of two cases with sCJD in the CTE Center series of 55 CTE cases by chance alone would be highly unlikely (p = 8.93*10− 6). Nevertheless, examination of a larger cohort of CTE is required to conclusively determine whether the risk of CJD is significantly increased in patients with CTE.